Impact of biomass burning sources during the high season on PM2.5 pollution observed at sampling sites in Hanoi, Vietnam and Chiang Rai, Thailand - Nguyen Duc Luong; Nares Chuersuwan; Hoang Tuan Viet; Bui Quang Trung (APN Science Bulletin, 2022)
This study aimed to assess PM2.5 concentration and the potential impacts of biomass burning sources on PM2.5 measured at the sampling sites in Hanoi, Vietnam and Chiang Rai, Thailand during the high season (from January to April) in 2021 in which intensive biomass burning activities occur in Southeast Asia (SEA) region. For this purpose, an integrated approach of PM2.5 in-situ measurement, receptor and trajectory modelling techniques and satellite remote sensing was employed. Results showed that the average value of PM2.5 daily concentrations measured at the sampling site in Hanoi was higher than that at the sampling site in Chiang Rai during January–February (winter) periods. In contrast, the average value of PM2.5 daily concentrations measured at the sampling site in Hanoi was slightly lower than the counterpart at the sampling site in Chiang Rai during March–April (spring) periods. Elevated concentrations of PM2.5 measured in Chiang Rai during March–April periods were largely associated with intensive biomass burning activities in the SEA region. Positive Matrix Factorisation (PMF) receptor model-based source apportionment results indicated a larger contribution of biomass burning sources to the PM2.5 measured at the sampling site in Chiang Rai compared to that at the sampling site in Hanoi. Analysis of MODIS cumulative fire radiative power maps in the SEA region and three-day air masses backward trajectories arrived at the sampling sites in Hanoi and Chiang Rai further suggested the potential impacts of biomass burning sources on the PM2.5 measured at the sampling sites in Hanoi during the winter periods and in Chiang Rai during the spring periods.